2020
DOI: 10.24189/ncr.2020.019
|View full text |Cite
|
Sign up to set email alerts
|

A global systematic review on orchid data in Protected Areas

Abstract: A systematic global literature review of studies devoted to Orchidaceae taxa in Protected Areas is presented here. It is aimed to understand research topics of studies on orchids in Protected Areas around the world. Used is the methodology well established in biological and medical science with a focus on two international databases (Scopus, Web of Science Core Collection) and one national (Russian Science Citation Index). Examined are the data on each paper's Protected Area location, habitat studied, topic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…This is in accordance with data on other studies demonstrated the high vulnerability of orchids in various regions around the world (e.g. [8,16,17]).…”
Section: Subsectionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with data on other studies demonstrated the high vulnerability of orchids in various regions around the world (e.g. [8,16,17]).…”
Section: Subsectionsupporting
confidence: 93%
“…In particular, this concerns data on conservation and distribution of orchids. For instance, Khapugin (2020) [8] demonstrated that despite numerous studies of orchids in Protected Areas, there is a remarkable gap of data in Russia, even taking into account a high number of Protected Areas in this country.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we concentrate on orchids, because orchids are considered to be one of the most threatened groups of species worldwide [18][19][20]. With approximately 28,500 species [21], Orchidaceae is one of the most diverse and widespread families of flowering plant [18].…”
Section: Introductionmentioning
confidence: 99%
“…Efimov [17] published a checklist of 135 orchid species in Russia, with a distribution pattern based on administrative regions. Moreover, Khapugin [22] summarized the global orchid distribution within protected areas based on published data, with the exception of Mongolia, owing to the lack of information. Hence, we aimed to fill this gap based on the revision of comprehensive herbariums and literature, as well as field observation data.…”
Section: Introductionmentioning
confidence: 99%